The Issue of the Commercial Court Limited Competency in Settling the Commercial Disputes - Sobandi Sobandi (Faculty of Law, Sriwijaya University, Indonesia, 2019)
The people’s need for justice through a special court is perceived urgent from time to time. The Commercial Court is an ad-hoc court but its competency has affected the competency of other permanent courts that are already established. The problems need to be answered in this writing regarding the multifunction of Commercial Court. The objectives of the writing, inter alia, to examine the possibility of the Commercial Court has specific rules to restrain its competency. Consequently, there is a need to have a law that specifically limits the competence and the procedural law of the ad-hoc court. The Commercial Court often resolves bankruptcy disputes. It is also used as a solution for the Intellectual Property Rights (IPR) disputes which should be able to enter the criminal domain. It can also be used to solve the Islamic financing issues and other business issues that should be the realm of a permanent judicial institution. The existence of such a rule that limits the competency of the Commercial Court can be a way out of fulfilment of needs of the judiciary to reduce the overlap of court competency among the Indonesian judicial institutions